Optical coherence tomography visualization of stent deformation with subsequent thrombus adhesion at very early phase after everolimus-eluting stent implantation: a case report - Yamamura, Satoru (BMC Cardiovasc Disord, 2016)
BACKGROUND: Stent malapposition, stent fracture, and deformity, and inadequate anti-thrombotic therapy are known as the risk of stent thrombosis. We report a case of stent deformation with subsequent thrombus adhesion at the site of a partial stent fracture detected by intravascular ultrasound (IVUS) and optical coherence tomography (OCT). CASE PRESENTATION: A 61-year-old male patient was diagnosed as effort angina pectoris. Coronary angiography revealed obstructions in the proximal segment of the left anterior descending (LAD) and left circumflex artery (LCx). Elective percutaneous coronary intervention (PCI) was scheduled for these lesions in the prior hospital. First, an everolimus-eluting stent (EES) was implanted in the just proximal LAD slightly protruding into left main trunk. One week later, the treatment to residual obstruction at proximal LCx was attempted. During delivery of the stent to LCx, the proximal edge of the previously-implanted LAD stent got stuck with the newly-deploying stent and deformed into the intravascular lumen when retracting the stent into the guide-catheter. He was immediately transferred to our hospital to repair these procedural problems. Two days later after the index procedure to LCx, intracoronary imaging with an IVUS and OCT were performed, and the IVUS/OCT imaging revealed thrombus adhesion around the deformed struts. The three-dimensional OCT guide also helped the detection of the deformed stent and the repair of deformed struts by additional stenting and kissing balloon technique. CONCLUSION: The current case suggested that thrombus adhesion can occur at the site of deformed and/or fractured stent at very early phase after stent implantation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12872-016-0295-2) contains supplementary material, which is available to authorized users.